A experiência de construção e organização da educação (escolar) indígena entre os Jenipapo-Kanindé, Aquiraz/Ceará - Santos, Vilyvia Carla Marques dos (2022)
The Indigenous Schools in Brazil emerged from the struggle indigenous movement in favor of Land, Health and Education that met their specificities and respected their local culture. Thus, indigenous school education modality was created, guaranteed by the Federal Constitution of 1988, since for decades education was used as a form of national domination and integration, denying to indigenous people even the right to their identities, beliefs, languages, customs and cultures. Therefore, this research seeks to understand the experience of indigenous school education among the Jenipapo-Kanindé (JK) people, who inhabit the Lagoa Encantada Indigenous Land (TI) in the municipality of Aquiraz - Ceará. For this purpose, this investigation presents a school education experience at the Jenipapo-Kanindé Indigenous School (EIJK) in its various contexts, including the remote/hybrid teaching experience and the educational boundaries that exist at the location. The study period comprises the interval between the years 2018 to 2021, in which circumstantial field visits was realized for initial investigations, bibliographic survey, monitoring of the EIJK's social networks, non-face to face interviews (online) and face-to-face interviews, as well as immersion in the field of ethnographic character. Seeking to contribute to debates in the field of anthropology and education.